Canada : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper looks at the factors behind the accumulation of cash positions by Canadian nonfinancial corporations. Focusing only on listed firms and running a model of changes in cash holdings suggest that greater macroeconomic and business uncertainty may have induced firms to raise the cash buffer at their disposal over the last decade. This is especially the case for firms in the energy and mining sector, which account for the majority of cash accumulation in the sample used in current analysis. The analysis also shows that firms' high cash balances are typically associated with higher levels of capital expenditure, which bodes well for the acceleration of business investment in the near future.